2011
DOI: 10.1371/journal.pone.0025145
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Historical Fish Community Composition Using Surveys, Historical Collection Data, and Species Distribution Models

Abstract: Accurate establishment of baseline conditions is critical to successful management and habitat restoration. We demonstrate the ability to robustly estimate historical fish community composition and assess the current status of the urbanized Barton Creek watershed in central Texas, U.S.A. Fish species were surveyed in 2008 and the resulting data compared to three sources of fish occurrence information: (i) historical records from a museum specimen database and literature searches; (ii) a nearly identical survey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 54 publications
0
24
0
Order By: Relevance
“…Distribution models for fish species regularly include variables of temperature, precipitation, drainage area, elevation, stream slope, discharge, land use, width, depth, and geology (Leathwick et al, 2005;Lassalle et al, 2008;Buisson & Grenouillet, 2009;Lyons et al, 2010;Steen et al, 2010;Bond et al, 2011;Labay et al, 2011;Wenger et al, 2011). It is possible that the particular variables were removed for having little influence on model performance that actually have strong impacts on species distributions at different scales.…”
Section: Model Development and Evaluationmentioning
confidence: 99%
See 2 more Smart Citations
“…Distribution models for fish species regularly include variables of temperature, precipitation, drainage area, elevation, stream slope, discharge, land use, width, depth, and geology (Leathwick et al, 2005;Lassalle et al, 2008;Buisson & Grenouillet, 2009;Lyons et al, 2010;Steen et al, 2010;Bond et al, 2011;Labay et al, 2011;Wenger et al, 2011). It is possible that the particular variables were removed for having little influence on model performance that actually have strong impacts on species distributions at different scales.…”
Section: Model Development and Evaluationmentioning
confidence: 99%
“…A variety of species distribution modeling approaches have been used to project fish distributions, including GLM (Lassalle et al, 2008;Wenger et al, 2011), GAM (Brosse & Lek, 2000Buisson et al, 2008;Lassalle et al, 2008), CTA (Lyons et al, 2010;Steen et al, 2010), and MAXENT (Labay et al, 2011). The ensemble modeling approach, however, has not been widely applied to fish species (but see Buisson & Grenouillet, 2009;Grenouillet et al, 2011;Poulos et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The high coherency between the two methods validates the use of historical fish species composition as a tool to esti- mate anthropogenic pressure. We used acidification as an example, and we are convinced that this approach can be used with other species to address other environmental concerns in other regions than Sweden, such as; climate change (Hein et al, 2012), effects of land alterations (Nilsson et al, 2005;Labay et al, 2011), and other airborne pollutants. The analysis showed that 64 lakes were not classified as acidified using either MAGIC or roach observations ( Fig.…”
Section: Lakes With Consistent Classificationmentioning
confidence: 99%
“…Given the extent of the population losses, the extinction was probably caused by EDCs, although this hypothesis remains to be confirmed. In recent years, several models were developed based on historical data and museum records, and connections between EDC pollution and species extinction have been found Duffy, 2011;Labay et al, 2011). Barnosky et al (2011) confirmed that environmental pollution is one possible cause of biodiversity decline.…”
Section: Evaluation Of the Hypothesismentioning
confidence: 86%